Spectrum conversion antireflection coating solution, preparation method and application thereof
Patent Information
- Application Number
- CN202611209991.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]但上述技术路线仍存在明显局限:稀土材料资源稀缺、成本高昂,不利于光伏产品大规模量产与成本控制;且稀土离子特征发射峰可调性差,难以与钙钛矿电池的最佳响应波段精准匹配
本发明无需基底钢化处理,可兼容碳点类下转换材料,利用材料与膜层之间的光学协同作用,在保证高透光性的前提下,显著提升膜层的光转换效率与光利用效率。
Smart Images

Figure CN122917577A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photovoltaic technology, and in particular to a spectral conversion antireflection coating solution, its preparation method, and its application. Background Technology
[0002] Energy shortages and environmental protection have become core issues in technological development and industrial upgrading in the new century. Solar energy, with its advantages of being clean, renewable, and widely distributed, has become a key direction for global energy structure transformation, and photovoltaic power generation is the most important form of large-scale solar energy utilization. In recent years, perovskite solar cells, with their outstanding advantages such as low manufacturing cost, high photoelectric conversion potential, and flexibility, have been regarded as one of the most promising next-generation photovoltaic technologies for industrialization. Their certified power conversion efficiency (PCE) has rapidly increased from 3.8% in 2009 to the current 26.1%, demonstrating extremely strong development potential and application value.
[0003] However, perovskite solar cells still face two major bottlenecks limiting their performance and lifespan in the process of moving towards practical outdoor applications. First, their narrow spectral response range results in low solar energy utilization. The intrinsic bandgap structure of the perovskite active layer determines its primary response region in the visible light spectrum. However, ultraviolet light accounts for approximately 5-8% of the solar spectrum, while infrared light accounts for a high 48-50%. A large number of high-energy short-wavelength and low-energy long-wavelength photons cannot be effectively utilized, fundamentally limiting further improvements in short-circuit current and overall conversion efficiency. Second, ultraviolet radiation causes device stability degradation. High-energy ultraviolet photons easily induce lattice instability, ion migration, and interface oxidative degradation in the perovskite active layer, accelerating the aging and failure of the charge carrier transport layer. Related studies show that perovskite devices without ultraviolet protection experience efficiency degradation exceeding 30% after 300 hours of simulated ultraviolet irradiation outdoors, severely restricting the long-term reliability and outdoor lifespan of the cells.
[0004] Down-conversion luminescent materials can convert high-energy short-wave ultraviolet light into visible light, which is sensitive to perovskite solar cells, simultaneously realizing the utilization of ultraviolet light resources and shielding against ultraviolet light damage. This has become an important technical path to improve the efficiency and stability of photovoltaic devices. Currently, common down-conversion systems mainly consist of rare-earth-doped oxides and semiconductor quantum dots. Previous studies have introduced rare-earth-doped materials into anti-reflection coating solutions, achieving ultraviolet-visible spectral conversion through tempering film formation, thus improving light utilization to a certain extent. Simultaneously, introducing luminescent sensitizers into the coating system can enhance the fluorescence intensity of the down-conversion material through energy transfer, further improving the light conversion effect.
[0005] However, the aforementioned technical routes still have significant limitations: rare earth materials are scarce and expensive, which is not conducive to the large-scale mass production and cost control of photovoltaic products; moreover, the characteristic emission peaks of rare earth ions have poor tunability, making it difficult to accurately match them with the optimal response band of perovskite solar cells. Therefore, developing novel downconversion materials with low cost, high fluorescence efficiency, and good compatibility with coating solutions, and constructing a room temperature curing coating system that combines light conversion function and antireflection performance, has become an important research direction and industrial challenge for improving the performance of perovskite photovoltaic devices. Summary of the Invention
[0006] To address the aforementioned problems, this invention provides a spectral conversion antireflection coating solution, its preparation method, and its application.
[0007] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing a spectral conversion antireflection coating solution, wherein the spectral conversion antireflection coating solution comprises an independently packaged base coating solution and a top coating solution, and includes the following steps: 1) Urea, phenolic substances and solvents are mixed and subjected to a thermal reaction to obtain a crude product; 2) Dialyze the crude product obtained in step 1), and freeze-dry it to obtain carbon dots; 3) Mix tetraethyl orthosilicate and solvent, adjust the pH to 2.0, and then hydrolyze to obtain hydrolysate; 4) Mix the carbon dots described in step 2) and the hydrolysate described in step 3) to obtain the base coating solution; 5) Mix silica sol, potassium silicate, organic compound, surfactant and solvent to obtain surface coating solution.
[0008] Preferably, in step 1), the volume ratio of the amount of urea, the amount of phenolic substances, and the solvent is 1.8 mol: 1 mol: 10 mL. The phenolic substances include catechol; The solvent includes N,N-dimethylformamide.
[0009] Preferably, the conditions for the hydrothermal reaction in step 1) include: a temperature of 200~240℃ and a time of 6h.
[0010] Preferably, the dialysis conditions in step 2) include: dialysis with ultrapure water for 24 hours in a dialysis bag with a molecular weight cutoff of 1000 Da.
[0011] Preferably, the solvent in step 3) includes ethanol and water; The molar ratio of tetraethyl orthosilicate to ethanol and water is 1:20:40; Use hydrochloric acid to adjust the pH value; The hydrolysis time shall be no less than 2 hours.
[0012] Preferably, the mass ratio of carbon dots to hydrolysate in step 4) is 1:15~30.
[0013] Preferably, in step 5), the mass ratio of silica sol, potassium silicate, organic compound, surfactant, and solvent is 15:100:0.3~0.6:0.1:1130. The particle size of the silica sol is 40~60nm; The organic compounds include polyvinyl alcohol and / or fluorocarbon emulsions; The surfactant is a surfactant of model ZY-2281 from Shanghai Ziyi Chemical Co., Ltd. The solvent comprises water and ethanol, wherein the mass ratio of water to ethanol is 1:1.
[0014] The present invention also provides a spectral conversion antireflection coating solution prepared by the preparation method described in the above technical solution.
[0015] The present invention also provides the application of the spectral conversion antireflection coating solution described above in substrate coating.
[0016] Preferably, the application includes the following steps: The substrate is immersed in the base coating solution of the spectral conversion antireflection coating solution for 20 seconds and then lifted up at a lifting speed of 2000~4000µm / s. After curing, the coating is immersed in the spectral conversion antireflection coating solution for 20 seconds and then lifted at a speed of 3000µm / s. The substrate includes ordinary float glass.
[0017] Beneficial effects: This invention does not require substrate tempering and is compatible with carbon dot downconversion materials. By utilizing the optical synergy between the material and the film, it significantly improves the light conversion efficiency and light utilization efficiency of the film while ensuring high light transmittance.
[0018] Carbon dots, as a novel type of environmentally friendly, low-cost, and optically tunable fluorescent nanomaterial, possess excellent ultraviolet absorption and visible light down-conversion luminescence properties. They can convert ultraviolet light, which perovskite solar cells cannot effectively utilize, into efficiently captured visible light, significantly improving photon utilization. Simultaneously, the surface of carbon dots is rich in functional groups such as hydroxyl and carboxyl groups, exhibiting good compatibility with conventional coating solution precursor systems, resisting aggregation, and facilitating uniform dispersion. Introducing carbon dots into the coating solution provides a dual function of "ultraviolet filtration + spectral modulation," reducing the structural damage of high-energy ultraviolet light to perovskite devices from the source and improving the long-term stability of the devices.
[0019] Matrix materials such as SiO2 possess moderate refractive index and excellent optical transmittance. By controlling the film composition and film thickness, a highly efficient antireflection layer can be formed, further improving the incident light transmittance and creating a synergistic effect with the light conversion function of carbon dots. This invention combines carbon dot-based downconversion luminescent materials with a base coating system and integrates them into a room-temperature curing topcoat solution. This allows for simultaneous antireflection, light conversion, and UV protection without altering the original battery manufacturing process or adding complex post-processing steps. It provides a simple and efficient technical solution to address the common problems of low light utilization and poor UV stability in perovskite solar cells.
[0020] In this invention, the carbon dots, as a key optical modifying additive, exhibit excellent ultraviolet-visible downconversion luminescence properties. They can efficiently absorb ultraviolet light below 400 nm and achieve photon conversion, directionally emitting visible light in the 450 nm band. The effective absorption bands of the carbon dots for ultraviolet light include typical bands such as 320 nm, 330 nm, 340 nm, 350 nm, 360 nm, 370 nm, 380 nm, and 390 nm, but are not limited to these specific values; they also exhibit corresponding downconversion light response characteristics for other ultraviolet bands below 400 nm.
[0021] In this invention, the polysilicate component (potassium silicate) forms a three-dimensional network cross-linked structure after room temperature curing. This structure effectively improves the density and structural stability of the film, thereby endowing the film with excellent hardness and wear resistance. The small-particle silica sol added to the coating solution has a particle size that matches the scattering threshold of visible and near-ultraviolet light, effectively reducing light scattering loss inside the film. At the same time, the nanoscale particles of silica sol can fill the micropores of the film, making the optical interface between the film surface and the interior more uniform, thus significantly improving the optical transmittance of the film. This invention does not require tempering of the substrate, breaking through the limitations of tempering process on the selection of downconversion materials and greatly expanding the selection range of downconversion materials. Carbon dot downconversion materials can be adapted to be used in the film system of this invention. The photoresponse characteristics of carbon dot materials match the light transmittance characteristics of the film, and their downconversion emission band can complement the light transmission band of the film, producing an optical synergistic effect. While ensuring the high light transmittance of the film, it further improves the overall light conversion efficiency and light utilization efficiency of the film. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the embodiments will be briefly introduced below.
[0023] Figure 1 The image shown is a transmission electron microscope image of carbon dots in Embodiment 1 of the present invention, with a scale bar of 20 nm. Figure 2The UV-Vis absorption, fluorescence excitation, and emission spectra of the carbon dots in Example 1 of this invention are shown. Figure 3 The fluorescence emission spectra of the carbon dots in Example 1 of this invention at different excitation wavelengths; Figure 4 This is a transmission electron microscope image of the room temperature curing coating solution in Example 1 of the present invention, where the scale bar is 400 nm; Figure 5 This is a cross-sectional view of the film layer in Example 1 of the present invention, where the scale bar is 1µm; Figure 6 Transmittance diagrams for Examples 1-9 and Comparative Examples 1-6 of the present invention; Figure 7 The reflectance diagrams are for Example 1 and Comparative Examples 1-6 of the present invention. Detailed Implementation
[0024] This invention provides a method for preparing a spectral conversion antireflection coating solution, wherein the spectral conversion antireflection coating solution comprises an independently packaged base coating solution and a top coating solution, and includes the following steps: 1) Urea, phenolic substances and solvents are mixed and subjected to a thermal reaction to obtain a crude product; 2) Dialyze the crude product obtained in step 1), and freeze-dry it to obtain carbon dots; 3) Mix tetraethyl orthosilicate and solvent, adjust the pH to 2.0, and then hydrolyze to obtain hydrolysate; 4) Mix the carbon dots described in step 2) and the hydrolysate described in step 3) to obtain the base coating solution; 5) Mix silica sol, potassium silicate, organic compound, surfactant and solvent to obtain surface coating solution.
[0025] This invention involves mixing urea, phenolic substances, and a solvent, followed by a thermal reaction to obtain a crude product. In this invention, the preferred volume ratio of urea, phenolic substances, and solvent is 1.8 mol:1 mol:10 mL. Preferably, the phenolic substances include catechol. Preferably, the solvent includes N,N-dimethylformamide. The preferred conditions for the hydrothermal reaction are: a temperature of 200-240°C and a time of 6 hours.
[0026] In this invention, the crude product is dialyzed and then freeze-dried to obtain carbon dots. Preferably, the dialysis conditions include dialyzing with ultrapure water in a dialysis bag with a molecular weight cutoff of 1000 Da for 24 hours. The freeze-drying conditions include freezing under vacuum at a temperature of -80 to -50°C.
[0027] This invention involves mixing tetraethyl orthosilicate and a solvent, adjusting the pH to 2.0, and then hydrolyzing the mixture to obtain a hydrolysate. Preferably, the solvent comprises ethanol and water. The preferred molar ratio of tetraethyl orthosilicate to ethanol and water is 1:20:40. Hydrochloric acid is preferably used to adjust the pH, and its concentration is 12 mol / L. The hydrolysis time is preferably at least 2 hours. In this invention, the hydrochloric acid is used as a catalyst. The catalytic process not only significantly improves the storage stability and reaction controllability of the coating solution, but also allows for precise control of the final film structure density, surface roughness, and interfacial bonding strength by adjusting the type and concentration of acid. This provides a crucial chemical basis for preparing high-transmittance, high-hardness, and strong-adhesion underlying optical functional coatings.
[0028] This invention involves mixing the carbon dots and the hydrolysate to obtain a base coating solution. In this invention, the preferred mass ratio of the carbon dots to the hydrolysate is 1:15~30.
[0029] This invention mixes silica sol, potassium silicate, an organic compound, a surfactant, and a solvent to obtain a surface coating solution. In this invention, the preferred mass ratio of the silica sol, potassium silicate, organic compound, surfactant, and solvent is 15:100:0.3~0.6:0.1:1130. In this invention, the preferred particle size of the silica sol is 40~60 nm. In this invention, the silica sol is preferably S-40 from Guangdong Huihe Silicon Products Co., Ltd. In this invention, the organic compound preferably includes polyvinyl alcohol and / or fluorocarbon emulsion. In this invention, the fluorocarbon emulsion is preferably HF-610F from Beijing Runbo Hengtong Technology Co., Ltd. In this invention, the surfactant is preferably ZY-2281 from Shanghai Ziyi Chemical Co., Ltd. In this invention, the solvent preferably includes water and ethanol, and the preferred mass ratio of water to ethanol is 1:1. In this invention, the organic compounds are mainly used to improve the film-forming properties of the coating. They can adjust the rheological properties of the coating solution, enhance the wettability of the substrate, promote the continuous formation of the film during the curing process, and improve the adhesion and flexibility of the film. By introducing the above-mentioned preferred organic compounds, the mechanical integrity and applicability of the film can be significantly optimized while maintaining its optical properties, thereby obtaining a composite functional film with both high optical transmittance and good practical durability. In this invention, the average particle size of the selected silica sol (40–60 nm) is much smaller than the wavelengths of visible and near-infrared light (above 380 nm), and its particle size is only about 1 / 6 to 1 / 10 of the incident light wavelength, which fully satisfies the core condition of weak scattering in Rayleigh scattering theory, that is, the particle size of the scattering particles is much smaller than the incident light wavelength. Based on the aforementioned particle size design, the dispersion of silica sol in the topcoat coating solution composition effectively reduces its scattering of visible and near-infrared light, preventing problems such as increased haze and decreased light transmittance in the coating layer caused by scattering. This ensures that the topcoat coating layer possesses excellent optical properties, such as high light transmittance and low haze. Simultaneously, this particle size range also helps improve the compatibility of the silica sol component with other components in the topcoat coating solution (such as silicone resin and additives), reducing agglomeration and thus improving the film uniformity, density, and overall performance of the coating layer. In this invention, the solvent plays a role in dissolving and dispersing in the composition; at the same time, the viscosity, surface tension and rheological properties of the coating solution can be precisely controlled by adjusting the type and ratio of solvent to adapt to different coating process requirements; during the film formation process, the choice of solvent directly affects the evaporation rate, film shrinkage behavior and the compactness of the final structure; in addition, a suitable solvent combination can also ensure the compatibility of each component, prevent phase separation or particle aggregation, thereby ensuring the stability of the coating solution during storage and use, and ultimately promoting the formation of a uniform, highly transparent and well-bonded functional film.In this invention, the surfactant can significantly enhance the wetting and spreading performance of the coating solution on the substrate by reducing the surface tension of the system. At the same time, it can effectively prevent the aggregation of inorganic nanoparticles by utilizing the steric hindrance effect, thus maintaining the long-term stability of the colloidal system. During the film formation process, it can also regulate the solvent evaporation behavior, inhibit the formation of surface defects such as orange peel and pinholes, and ultimately improve the structural uniformity, surface quality and overall performance of the film by improving the interfacial compatibility of the inorganic-organic multiphase system.
[0030] The present invention also provides a spectral conversion antireflection coating solution prepared by the preparation method described in the above technical solution.
[0031] The present invention also provides the application of the spectral conversion antireflection coating solution described above in substrate coating.
[0032] In this invention, the application preferably includes the following steps: The substrate is immersed in the base coating solution of the spectral conversion antireflection coating solution for 20 seconds and then lifted up at a speed of 2500~3000µm / s. After curing, the coating is immersed in the spectral conversion antireflection coating solution for 20 seconds and then lifted at a speed of 3000µm / s. The substrate preferably includes float glass, and more preferably ordinary float glass from Zhejiang Haiken.
[0033] To further illustrate the present invention, the following detailed description is provided in conjunction with embodiments, but these should not be construed as limiting the scope of protection of the present invention.
[0034] Example 1 This embodiment of the spectral conversion antireflective coating solution includes separately packaged primer and topcoat solutions. The primer solution consists of carbon dots, tetraethyl orthosilicate, acid, and solvent. The topcoat is a room temperature curing solution composed of silica sol, polysilicate, organic compounds, solvent, and surfactant.
[0035] The preparation method includes the following steps: (1) Add 1.8 mol of urea and 1 mol of catechol to 10 mL of N,N-dimethylformamide and disperse evenly by ultrasonication. Transfer the resulting mixture to a 20 mL polytetrafluoroethylene-lined reactor, place the reactor in an oven, heat it to 240°C and keep it at that temperature for 6 h, and then allow it to cool naturally to room temperature to obtain the crude product.
[0036] The crude product was placed in a dialysis bag with a molecular weight cutoff of 1000 Da and dialyzed with ultrapure water for 24 h. After freeze-drying (vacuum, -80 to -50°C), carbon dots were obtained. Figure 1As shown, well-dispersed spherical nanoparticles with an average diameter of approximately 2-4 nm were obtained. Figure 2 and Figure 3 As shown, the emission peak of the carbon dots does not change with the excitation wavelength and is located at 450 nm, and there is no ultraviolet-visible absorption peak in the 400~800 nm band; according to the principle of spectral testing, the absence of absorption peaks indicates that the carbon dots do not absorb light in this band and do not interfere with the transmittance of the visible light band.
[0037] (2) Mix tetraethyl orthosilicate, ethanol, and water in a molar ratio of 1:20:40, and adjust the pH to 2.0 with hydrochloric acid (12 mol / L). Place the mixture in a magnetic stirrer and stir in a water bath at room temperature for at least 2 hours to ensure complete hydrolysis. Pour the hydrolyzed solution into a beaker for later use. Mix the hydrolysate with carbon dots in a mass ratio of 20:1, and disperse evenly by ultrasonication to obtain the primer coating solution.
[0038] (3) A mixture of silica sol (particle size 40~60nm), potassium silicate, polyvinyl alcohol (PVA), surfactant (ZY-2281 from Shanghai Ziyi Chemical Co., Ltd.), and solvent (water and ethanol in a mass ratio of 15:100:0.3:0.1:1130) in a mass ratio of 15:100:0.3:0.1:1130 is stirred evenly to obtain the surface coating solution. Figure 4 As shown, these are solid particles with a diameter of approximately 10-40 nm.
[0039] (4) Dip Coating: Place the substrate (5×10cm ordinary float glass) in an ultrasonic cleaner to remove stubborn stains from the surface; then use alcohol for precise wiping to ensure the product surface is clean and free of residue. The substrate is vertically fixed on the sample holder of the dip coating machine, keeping the substrate vertical and without tilting. Place the prepared base coating solution in a clean container, adjust the container position so that the center of the substrate is aligned with the center of the coating solution surface, and ensure that the substrate is fully immersed in the dip coating process without touching the container wall. Start the dip coating program, control the descent speed to 2000 µm / s, and vertically immerse the substrate in the base coating solution for 20 seconds to allow the base coating solution to fully wet and cover the substrate surface. Then, lift the substrate vertically upwards at a constant lifting speed of 2500 µm / s, keeping the liquid surface stable, without vibration or airflow disturbance during the lifting process, so that a 5 cm long and uniformly thick wet film is formed on the substrate surface. After the primer wet film has cured, fix the substrate vertically again, aligning the center of the substrate with the center of the topcoat liquid surface. Using the same operating parameters as the primer lifting (descent speed 2000 µm / s, immersion dwell time 20 s, lifting speed 3000 µm / s), complete the topcoat lifting at a uniform speed to ensure a uniform and flawless topcoat wet film thickness. Figure 5 As shown, the thickness of the base coating is 88.3 nm and the thickness of the top coating is 126 nm.
[0040] Example 2 The spectral conversion antireflective coating solution includes separately packaged primer and topcoat solutions. The primer solution consists of carbon dots, tetraethyl orthosilicate, acid, and solvent. The topcoat is a room-temperature curing solution composed of silica sol, polysilicate, organic compounds, solvent, and surfactant.
[0041] The preparation method includes the following steps: (1) Urea and catechol in a molar ratio of 1.8:1 were added to 10 mL of N,N-dimethylformamide and ultrasonically dispersed until homogeneous. The resulting mixture was transferred to a 20 mL polytetrafluoroethylene-lined reactor, which was placed in an oven and heated to 210°C for 6 h. After naturally cooling to room temperature, the crude product was obtained. The crude product was dialyzed in a dialysis bag with a molecular weight cutoff of 1000 Da for 24 h to obtain carbon dots.
[0042] (2) Mix tetraethyl orthosilicate, water, and anhydrous ethanol in a molar ratio of 1:20:40, place in a magnetic stirrer, and stir in a water bath for at least 2 hours to ensure complete hydrolysis. Adjust the pH to 2 with hydrochloric acid (12 mol). Pour the hydrolyzed solution into a beaker for later use. Mix the hydrolysate with carbon dots at a mass ratio of 20:1, and disperse evenly by ultrasonication to obtain the primer coating solution.
[0043] (3) Stir the mixture of silica sol, potassium silicate, cellulose, surfactant (ZY-2281 from Shanghai Ziyi Chemical Co., Ltd.) and solvent (water and n-propanol in a mass ratio of 15:100:0.6:0.1:1130) evenly to obtain the room temperature surface coating solution.
[0044] (4) Dip Coating: The pretreated and dried clean substrate is vertically fixed on the sample holder of the dip coating machine, keeping the substrate vertical and without tilt. The prepared primer coating solution is placed in a clean container, and the container position is adjusted so that the center of the substrate is aligned with the center of the coating solution surface, ensuring that the substrate is fully immersed in the dip coating process without touching the container wall. Start the dip coating program, control the descent speed to 2000 µm / s, and vertically immerse the substrate in the primer coating solution for 20 s to allow the primer coating solution to fully wet and cover the substrate surface. Then, the substrate is pulled vertically upward at a constant pulling speed of 2500 µm / s, keeping the liquid surface stable, without vibration or airflow disturbance during the pulling process, so that a wet film of uniform thickness is formed on the substrate surface. After the base coat wet film has cured, fix the substrate vertically again, aligning the center of the substrate with the center of the top coat coating liquid. Use the same operating parameters as the base coat lifting (descent speed 2000 µm / s, immersion dwell time 20 s, lifting speed 3000 µm / s) to complete the top coat lifting at a uniform speed, ensuring that the top coat wet film thickness is uniform and without defects.
[0045] Example 3 This embodiment provides a spectral conversion antireflection coating solution and its preparation method. Except for replacing the organic compound in the surface coating solution with an equal mass of fluorocarbon emulsion (HF-610F from Beijing Runbo Hengtong Technology), the other steps and conditions are the same as in Example 1, so they will not be described in detail here.
[0046] Example 4 This embodiment provides a spectral conversion antireflection coating solution and its preparation method. Except for replacing the carbon dot preparation temperature with 220°C, the other steps and conditions are the same as in Example 1, so they will not be described in detail here.
[0047] Example 5 This embodiment provides a spectral conversion antireflection coating solution and its preparation method. Except for replacing the carbon dot preparation temperature with 200°C, the other steps and conditions are the same as in Example 1, so they will not be described in detail here.
[0048] Example 6 This embodiment provides a spectral conversion antireflection coating solution and its preparation method. Except for replacing the mass ratio of the base hydrolysate to carbon dots from 20:1 to 15:1, the other steps and conditions are the same as in Example 1, so they will not be described in detail here.
[0049] Example 7 This embodiment provides a spectral conversion antireflection coating solution and its preparation method. Except for replacing the mass ratio of the base hydrolysate to carbon dots from 20:1 to 30:1, the other steps and conditions are the same as in Example 1, so they will not be described in detail here.
[0050] Example 8 This embodiment provides a spectral conversion antireflection coating solution and its preparation method. Except for replacing the base coating lifting speed of 2500 µm / s with 2000 µm / s, the other steps and conditions are the same as in Example 1, so they will not be described in detail here.
[0051] Example 9 This embodiment provides a spectral conversion antireflection coating solution and its preparation method. Except for replacing the base coating lifting speed of 2500 μm / s with 4000 μm / s, the other steps and conditions are the same as in Example 1, so they will not be described in detail here.
[0052] Comparative Example 1 This comparative example provides a spectral conversion antireflection coating solution and its preparation method. Only the coating solution is lifted from the base coat without adding carbon dots, and the top coat is not lifted. The remaining steps are the same as in Example 1, so they will not be described in detail here.
[0053] Comparative Example 2 This comparative example provides a spectral conversion antireflection coating solution and its preparation method. Only the carbon dots for coating are lifted (the carbon dot solution is obtained by mixing ultrapure water and carbon dots at a mass ratio of 20:1). The other steps are the same as in Example 1, so they will not be described in detail here.
[0054] Comparative Example 3 This comparative example provides a spectral conversion antireflection coating solution and its preparation method. Only the bottom coating solution with added carbon dots is lifted. The other steps are the same as in Example 1, so they will not be described in detail here.
[0055] Comparative Example 4 This comparative example provides a spectral conversion antireflection coating solution and its preparation method. Except for the absence of carbon dots in the base coating solution, the other steps and conditions are the same as in Example 1, and therefore will not be repeated here.
[0056] Comparative Example 5 This comparative example provides a spectral conversion antireflection coating solution and its preparation method. Only the coating solution is applied to the coating surface by lifting. The other steps and conditions are the same as in Example 1, so they will not be described in detail here.
[0057] Comparative Example 6 This comparative example uses a raw glass sheet without any coating solution.
[0058] Performance comparison: The coated glasses of Examples 1-9 and Comparative Examples 1-6 were subjected to transmittance tests, hardness tests, and weather resistance tests (referencing JC T 2170-2013 Antireflective Coating Glass for Solar Photovoltaic Modules). The results are as follows: Figure 6 As shown in Table 1.
[0059] Table 1 Test Results Combined with Table 1 Figure 6 The test results show that, compared with the original glass sheet (Comparative Example 6), Example 1 exhibits a 1.8% increase in transmittance in the 380-760nm range, demonstrating the material's anti-reflective properties. Compared with the carbon-dot-free double-coated sample (Comparative Example 4), Example 1 shows a 2% decrease in transmittance at 365nm, while its transmittance in the visible light region increases by 0.3%, indicating that more ultraviolet light is converted into visible light, demonstrating significant light conversion characteristics. Simultaneously, the introduction of carbon dots can achieve multiple functions such as anti-reflection, light conversion, and ultraviolet protection, thereby improving the photoelectric conversion efficiency and long-term stability of photovoltaic modules. In the photovoltaic coating industry, even a 0.1% fluctuation in transmittance is considered significant.
[0060] Figure 7The reflectance spectra of photovoltaic glasses with different coating structures are shown. The uncoated original glass (Comparative Example 6) and the sample coated with only a single layer of carbon dots (Comparative Example 2) have the highest reflectance, both greater than 8.0%, indicating that a single layer of carbon dots alone cannot achieve the ideal anti-reflection and light conversion effect. For the single-layer base coating samples, the carbon doped base coating sample (Comparative Example 3) has a lower reflectance than the base coating sample without carbon dots (Comparative Example 1), and forms a significant reflection trough at a wavelength of 450 nm. The lower the reflectance, the higher the transmittance in the corresponding wavelength band. This phenomenon indicates that carbon dots can absorb ultraviolet light and convert it into visible light near 450 nm, improving the transmittance level in this wavelength band and reducing reflection, directly proving that carbon dots have a light conversion function. With only a top coating (Comparative Example 5), the reflectance drops to ~6.8%. After adopting a dual-layer composite coating structure of primer and topcoat, the reflectivity of the samples was significantly optimized (Comparative Example 4 and Example 1). Among them, the sample with carbon dots in the primer and topcoat (Example 1) had the lowest reflectivity in all visible light bands and the best anti-reflection performance, with the reflectivity reduced to 6.3%. The introduction of carbon dots in the primer effectively reduced the reflectivity of the photovoltaic glass, which is beneficial to improving the light capture efficiency of the photovoltaic module.
[0061] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a spectral conversion antireflective coating solution, wherein the spectral conversion antireflective coating solution comprises separately packaged primer coating solution and topcoat coating solution, characterized in that, Includes the following steps: 1) Urea, phenolic substances and solvents are mixed and subjected to a thermal reaction to obtain a crude product; The crude product obtained in step 1) was dialyzed and freeze-dried to obtain carbon dots. Tetraethyl orthosilicate and solvent were mixed, and the pH was adjusted to 2.0 before hydrolysis was carried out to obtain the hydrolysate. Mix the carbon dots described in step 2) and the hydrolysate described in step 3) to obtain the base coating solution; A surface coating solution is obtained by mixing silica sol, potassium silicate, organic compounds, surfactants, and solvents.
2. The preparation method according to claim 1, characterized in that, Step 1) The volume ratio of urea, phenolic substances, and solvent is 1.8 mol: 1 mol: 10 mL; The phenolic substances include catechol; The solvent includes N,N-dimethylformamide.
3. The preparation method according to claim 1, characterized in that, The conditions for the hydrothermal reaction in step 1) include: a temperature of 200~240℃ and a time of 6h.
4. The preparation method according to claim 1, characterized in that, Step 2) The dialysis conditions include: dialysis with ultrapure water for 24 hours in a dialysis bag with a molecular weight cutoff of 1000 Da.
5. The preparation method according to claim 1, characterized in that, Step 3) The solvents include ethanol and water; The molar ratio of tetraethyl orthosilicate to ethanol and water is 1:20:40; Use hydrochloric acid to adjust the pH value; The hydrolysis time shall be no less than 2 hours.
6. The preparation method according to claim 1, characterized in that, Step 4) The mass ratio of carbon dots to hydrolysate is 1:15~30.
7. The preparation method according to claim 1, characterized in that, In step 5), the mass ratio of silica sol, potassium silicate, organic compound, surfactant, and solvent is 15:100:0.3~0.6:0.1:1130. The particle size of the silica sol is 40~60nm; The organic compounds include polyvinyl alcohol and / or fluorocarbon emulsions; The solvent comprises water and ethanol, wherein the mass ratio of water to ethanol is 1:
1.
8. A spectral conversion antireflection coating solution prepared by the preparation method according to any one of claims 1 to 7.
9. The application of the spectral conversion antireflection coating solution according to claim 8 in substrate coating.
10. The application according to claim 9, characterized in that, The application includes the following steps: The substrate is immersed in the base coating solution of the spectral conversion antireflection coating solution for 20 seconds and then lifted up at a lifting speed of 2000~4000µm / s. After curing, the coating is immersed in the spectral conversion antireflection coating solution for 20 seconds and then lifted at a speed of 3000µm / s. The substrate includes ordinary float glass.